Violência intrafamiliar contra crianças: cotidiano e possibilidades de enfrentamento - Albuquerque, Isis de (Universidade Federal de São Carlos, 2015)
Child violence is a phenomenon difficult to notify, prevent and intervene on since it encompasses legal, economic, social, political and cultural issues, and whose complexity increases when it is intrafamilial, once it occurs among members oscillating between the roles of tutors and aggressors. Aiming to ensure the rights and, consequentially, the prevention of child violence, the Child and Adolescent Statute (ECA) includes right-ensuring actions to be enforced by a full protection network. Among the services offered by this network, the present study highlights the Specialized Centre of Reference for Social Assistance (CREAS), which offers specialized assistance to families and individuals in personal or social risk for violation of rights. Considering how relevant is the comprehension of the everyday life of these families and how violence is experienced in this context, this study had the objective of identifying how those linked to CREAS understand and face violence situations in their daily routines. Fourteen relatives, responsible for the daily cares of children and teenagers victims of family violence assisted by the CREAS of a large-sized city in the interior of São Paulo State, participated to the study. The instruments used to collect data were an identification form, a sociodemographic questionnaire, the Social Support Questionnaire (SSQ) as well as a guide for semi-structured interviews. The data analysis related to the questionnaires was descriptive and that concerning the interviews was performed according to Bardin s content analysis. The results of this study indicated that relatives implemented protective actions towards the children and the family and made attempts to live a daily life without violence. It was highlighted that risk factors present in the daily life of these families, such as social isolation, limited social support and financial vulnerability, associated with the fragmented action of the protection network, may compromise the effectiveness of the actions attempted by the responsible relatives in order to fight violence and, among other aspects, that it is impossible for the family to make the protective actions effective and maintain them over time without support from the community and the services. The results also pointed out the need to strengthen and articulate the protective network as well as to enhance its actions by incorporating to it specialized treatment services for the aggressor and expertise of child violence.
Keywords: Terapia ocupacional; Violência intrafamiliar; Fatores de risco e proteção; Cotidiano; Suporte social; Rede de proteção integral; CREAS; Intrafamilial violence; Social support; Daily life; Protection Network; Risk and protection factors; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL